Developments of Advanced Electrospinning Techniques: A Critical Review. Issue 11 (14th July 2021) - Li, Ya; Zhu, Jiadeng; Cheng, Hui; Li, Guoqing; Cho, Hyunjin; Jiang, Mengjin; Gao, Qiang; Zhang, Xiangwu
Abstract: Electrospinning, considered as a low‐cost and straightforward approach, attracts tremendous attention because nanofibrous materials with functional properties prepared by it can be widely applied in numerous fields, including rechargeable batteries, filtration, and distillation. This paper aims to provide a comprehensive review of the latest advances in developing this unique technique, which starts with a brief introduction of the advantages of electrospinning and highlights ongoing research activities, followed by its principles and progress. Afterward, the corresponding properties of electrospun nanofibers are discussed. A future vision regarding challenges and perspectives in this area is proposed at the end. It is believed that this review would provide an extensive and comprehensive reference to utilize this advanced technique to generate novel nanofibers performing in high demanding areas. Abstract : This review aims to provide comprehensive and critical aspects related to recent developments in electrospinning techniques. It briefly describes this novel technique's uniqueness, followed by its principles and progress, summarizing the general mechanism and important parameters that may affect nanofibers' properties. In the end, the current achievements, research challenges, and future perspectives are also given.